Statisticheskaya ekspertnaya sistema "Sorevnovaniya po karate-do dlya podgotovki sudei, trenerov i sportsmenov k sorevnovaniyam - Dmitryev, O. B.; Akhmedzyanov, E. R. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The construction of the multimedia expert statistical system (ESS) "Karate-Do Competitions" is considered in this article. The ESS in basing on methods of the qualimetry and application of it as the educating-supervising system and the training equipment for the professional skills of the physical culture and sports specialists training (on an example of the Karate referees). The conceptual tendency of the application of the information technologies in the area of physical culture and sports: 1. The multimedia expert statistical systems allows to organise the reference and the trainee modes of functioning of the computer environment, and the statistical analysis of the professional skills of the user, formation of the general sample of opinions of the experts-users and definition of the statistical characteristics on the each element of the database. 2. As the "standards" the most typical and characteristic problem situations reflecting the different items of rules of competitions get out. 3. The average selective values are formed for all groups of the subjects of competitions: referees, coaches and athletes.